ANALISIS PENGARUH FAKTOR PENYEBAB STRES KERJA SECARA INDIVIDUALTERHADAP PRESTASI KERJA KARYAWAN BAGIAN OPERASIONAL PADA PT. SAMUDRA INDONESIA CABANG SURABAYA (Research Institution and Community Service Wijaya Kusuma Surabaya University, 2004)
A personality manager of an organization is demand to produce a competen employee and also can manage all department, although in the accomplishment process is found in conflict between an organization importance and the employee, so that can be influence the work of employee and it caused of their success work. There was a sample of 600 employees in United State of America, which showed that 46 percent of their work was stresfull and 34 percent reported that stres was the worst, so they trought to quite from their job (A. Farnham,